2017
DOI: 10.1002/cctc.201700980
|View full text |Cite
|
Sign up to set email alerts
|

Diastereoselective Cyclization of 1,5‐Dienes with the C−H Bond of Pyridine Catalyzed by a Cationic Mono(phosphinoamide) Alkyl Scandium Complex

Abstract: The carbocyclization of non-conjugated dienes mediated by organometallicsi sa ni mportant reaction for the synthesis of a variety of carbocyclic derivatives, but the directa nnulation of dienes with an inert CÀHbond of asubstrate has remained unexplored to date. We herein report as eries of novel rare-earth dialkyl complexes bearing ap hosphinoamide anion and demonstrate that the combination of am ono(phosphinoamido)-ligated scandium dialkyl complex with B(C 6 F 5 ) 3 resultsi na ne xcellent catalyst for the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 71 publications
1
8
0
Order By: Relevance
“…Thereafter, the group of Hou succeeded in the carbocyclization of non-conjugated dienes 39 by means of scandium dialkyl complex 40 (Scheme ). Here, the catalytic system consisted of equimolar quantities of 40 and B­(C 6 F 5 ) 3 , which efficiently catalyzed the cis -cyclization of 1,5-dienes 39 with the ortho -C–H bond of pyridines 29 . The authors proposed a plausible catalytic cycle for the cis -selective cyclization, as shown in Scheme .…”
Section: Scandiummentioning
confidence: 99%
“…Thereafter, the group of Hou succeeded in the carbocyclization of non-conjugated dienes 39 by means of scandium dialkyl complex 40 (Scheme ). Here, the catalytic system consisted of equimolar quantities of 40 and B­(C 6 F 5 ) 3 , which efficiently catalyzed the cis -cyclization of 1,5-dienes 39 with the ortho -C–H bond of pyridines 29 . The authors proposed a plausible catalytic cycle for the cis -selective cyclization, as shown in Scheme .…”
Section: Scandiummentioning
confidence: 99%
“…Although the above proposed mechanism could schematically explain the products obtained experimentally, many details remained unclear, such as structural information on the active catalyst species, key intermediates and transition states, the energy profiles of the reaction processes, and rationale for the observation that C–H activation is the rate-determining step. Moreover, although the C–H functionalization of various heteroatom-containing substrates with alkenes catalysed by rare-earth complexes have been widely reported, 5–11 whether or how a heteroatom-containing substrate would influence the coordination or insertion of an alkene at the catalyst metal center remained elusive. In order to clarify these important issues, we performed density functional theory (DFT) studies on the Sc-catalysed C–H alkylation of sulfides with alkenes and dienes.…”
Section: Introductionmentioning
confidence: 99%
“…In principle, the direct C–H addition of pyridines to unsaturated π-bonds is the most atom-economical method to synthesize pyridine derivatives . In these contents, rare-earth complexes have been demonstrated to serve as excellent catalysts for the C–H addition of pyridines with alkenes and imines to synthesize alkylated or aminoalkylated pyridine derivatives. , Encouraged by the unique performance of rare-earth catalysts in C–H functionalization, Hou and co-workers reported the C–H alkenylation of pyridines with allenes catalyzed by a half-sandwich scandium catalyst for the first time, which featured high regio- and stereoselectivity (1,2- E -selective product, Scheme a) . Based on experimental and theoretical reports, , a plausible mechanism was outlined in Scheme b.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it has received tremendous interest in organic synthesis . As an emerging field, cationic rare-earth (scandium, yttrium, and lanthanides) alkyl complexes have been found to be a powerful platform for the C–H addition of various heteroatom-containing substrates (such as pyridines, quinolines, aldimines, imidazoles, sulfides, anisoles, anilines, amines, and ferrocenes) to alkenes and alkynes in the past decade (Scheme ). Notably, these reactions often feature high regio-, stereo-, and chemo-selectivity, which are often superior or complementary to transition-metal catalysts due to their unique chemical reactivities .…”
Section: Introductionmentioning
confidence: 99%